2009
DOI: 10.1364/oe.17.005953
|View full text |Cite
|
Sign up to set email alerts
|

Circular Grating Resonators as Small Mode-Volume Microcavities for Switching

Abstract: We demonstrate the suitability of microcavities based on circular grating resonators (CGRs) as fast switches. This type of optical resonator is characterized by a high quality factor and very small mode volume. The waveguide-coupled CGRs are fabricated with silicon-on-insulator technology compatible with standard complementary metal-oxide semiconductor (CMOS) processing. The linear optical properties of the CGRs are investigated by transmission spectroscopy. From 3D finite-difference time-domain simulations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Similar findings have been concluded by Schönenberger et al by comparison to rigorous solutions to a rotationally symmetric setup. 1 We have exported field distributions for all near fields in the investigated wavelength range and we have found similar whispering-gallery-like resonances at all resonance frequencies with sharp features in the transmission spectrum. A wavelength for which the fundamental resonance with main field localization in the central disc would be excited has not been found in the investigated wavelength range.…”
Section: D Simulation Of Transmission Through a Circular Grating Resmentioning
confidence: 69%
See 2 more Smart Citations
“…Similar findings have been concluded by Schönenberger et al by comparison to rigorous solutions to a rotationally symmetric setup. 1 We have exported field distributions for all near fields in the investigated wavelength range and we have found similar whispering-gallery-like resonances at all resonance frequencies with sharp features in the transmission spectrum. A wavelength for which the fundamental resonance with main field localization in the central disc would be excited has not been found in the investigated wavelength range.…”
Section: D Simulation Of Transmission Through a Circular Grating Resmentioning
confidence: 69%
“…In a recent experiment, high-Q resonances and switching in such a devices, fabricated with silicon-on-insulator technology, have been demonstrated. 1 Rigorous 3D Maxwell solvers are helpful in the design of such structures, however, due to the complex structure of CGRs and due to the large volume of the computational domains, accurate computation of field distributions and Q factors in 3D CGR setups is numerically challenging. 1 In a recent publication it has been theoretically shown that CGRs in cylindrically symmetric setups allow to reach very high Q values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 a-b)). Such structure have successfully being used to confine photonic [22][23][24] and plasmonic [25][26][27] modes. The mechanical waves reflected by this circular grating can be understood using the onedimensional approximation shown in Fig.…”
mentioning
confidence: 99%
“…Radial Bragg Lasers (RBLs) belong to a unique class of circular resonator, which utilizes Bragg reflection as the transverse confinement mechanism, thus enabling the realization of high-Q-factor cavities with high mode-discrimination, while maintaining a wide control over the modal field profile and the device dimensions. Circular Bragg cavities and RBLs have been studied extensively by various groups [3][4][5][6][7][8][9][10][11][12][13], and a variety of RBL-based applications such as high-power semiconductor lasers, surfaceemitting lasers, rotation and bio-chemical sensors, etc. have been suggested and studied.…”
mentioning
confidence: 99%